THE EFFORT TO IMPROVE STUDENT MATH CONNECTIONS THROUGH OPEN-ENDED APPROACH IN MATHEMATICS LEARNING IN SMP NEGERI 10 SATU ATAP WONOSOBO - Agus Purwanto; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
This study was conducted because of the low ability to connect mathematics students in learning mathematics. The purpose of this study is to improve student math connections in the class of VIII SMP Negeri 10 Satu Atap Wonosobo regency in the academic year of 2015/2016 through an open-ended approach. The subjects were a student of class VIII SMP Negeri 10 Satu Atap Wonosobo regency in the academic year of 2015/2016 amounting to 12 students consisting of 5 male students and 7 female students. The object of this research is the process of learning mathematics through the open-ended approach. The study was conducted in three cycles. Data collection techniques used were observation, interview, test, field notes, and triangulation. Data collection instruments such as observation, interviews, test description that has been validated. Data were analyzed using qualitative descriptive analysis. The results showed that the learning of mathematics through an open-ended approach can improve student math connections in a class of VIII SMP Negeri 10 Satu Atap Wonosobo regency in the academic of 2015/2016. This is evident from the results of students’ mathematical ability test connection to the percentage indicator of the connection between mathematical topics in the first cycle of 41,67%, the second cycle of 61,11% and 75% the third cycle. Percentage indicators mathematical connections with other disciplines in the first cycle of 36,11%, 52,78% for the second cycle and the third cycle of 63,89%. Then the last percentage indicators mathematical connection with the daily life of 52,78% in the first cycle, the second cycle of 66,67% and 72,22% for the third cycle. Increased connections student mathematics good influence on the result of students’ mathematics learning.